2016
DOI: 10.1088/1361-6668/30/2/025010
|View full text |Cite
|
Sign up to set email alerts
|

General approach for the determination of the magneto-angular dependence of the critical current of YBCO coated conductors

Abstract: The physical understanding and numerical modelling of superconducting devices which exploit the high performance of second generation high temperature superconducting tapes (2G-HTS), is commonly hindered by the lack of accurate functions which allow the consideration of the in-field dependence of the critical current. This is true regardless of the manufacturer of the superconducting tape. In this paper, we present a general approach for determining a unified function Ic(B, θ), ultimately capable of describing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(52 citation statements)
references
References 16 publications
1
50
0
Order By: Relevance
“…Previously, we studied the angular-field dependence of critical current J c (θB) of YBCO tapes, which demonstrated that the magnitude and direction of the external DC magnetic field have significant impact on the critical current of studied samples [29]. Combining that conclusion with the present study, we believe that the DC background field might be able to accelerate the HF-assisted quench.…”
Section: Study Of Active Quench Under Various External DC Fieldssupporting
confidence: 79%
See 1 more Smart Citation
“…Previously, we studied the angular-field dependence of critical current J c (θB) of YBCO tapes, which demonstrated that the magnitude and direction of the external DC magnetic field have significant impact on the critical current of studied samples [29]. Combining that conclusion with the present study, we believe that the DC background field might be able to accelerate the HF-assisted quench.…”
Section: Study Of Active Quench Under Various External DC Fieldssupporting
confidence: 79%
“…In our previous research, we had generalized a fitting function which was capable of accurately describing I c (θB) relationship of 2G HTS tapes [29]:…”
Section: Field-angular Dependence Of the Critical Current Of The Studmentioning
confidence: 99%
“…The equation we derived is an extended version of the Kim model [16], which takes into account the material anisotropy and the flux-creep processes of YBCO samples [10]. Our approach can be generalized as…”
Section: Curve Fittingmentioning
confidence: 99%
“…To solve this problem, previously, we have measured the magneto-angular dependence of critical current density of five different YBCO commercial tapes [10]. During the fitting process of these results, the validity of our novel multi-objective model was successfully proved.…”
Section: Introductionmentioning
confidence: 98%
“…For the design of the HTS transformer, the critical current of the second generation coated conductor is about 300 A/cm at 77 K [9]. The perpendicular component of the magnetic field at the coil ends is estimated to be 0.18 T, which could reduce the critical current of the second generation (2G) HTS tapes to 200 A/cm.…”
Section: Introductionmentioning
confidence: 99%